Pomoc a postawa roszczeniowa - Wojciech Łaptaś (Przedsiębiorczość - Edukacja, 2006)
Entrepreneurs take advantage of all kind of help and they give it to others, as well. Help, in meaning as a peculiar instinct and impulse of solidarity in human relations, is very positive social reactions that encourage and stimulate development and progress. In spite of that kind of help there is also another one, which very often has a bad effect on society. The state offering unskillfully help and assistance to entrepreneurs make them, in most cases, lay claims to state. In such a situation entrepreneurs concentrate upon searching for loans, grant and subsidy instead of running their own company. To make matters worse, they make their success dependent on assistance and help from the state. In such situation responsibilities for theirs own existence are less important than awareness of being protected by the state. When the help for entrepreneurs is connected with the condescending behavior, it could cause negative attitude and assertion of claim and would result in growing disrespect of knowledge and new claims. Taking everything into account, help and assistance for entrepreneurs should be offered in a partnership way in order to the make a positive reflections and attitude to the market